This Review Recent Advances in Chitosan and Alginate‐Based Hydrogels for Wound Healing Application - Kibungu, Cuthbert; Kondiah, Pierre P. D.; Kumar, Pradeep; Choonara, Yahya E. (Frontiers in Materials, 2021)
Wound healing is a complicated yet necessary event that takes place in both animals and human beings for the body to repair itself due to injury. Wound healing involves various stages that ensure the restoration of the injured tissue at the end of the process. Wound dressing material acts as a protective extracellular barrier against potential damage to the injury and microbial invasion. Naturally, polysaccharides (chitosan and alginate) have inherent properties that have made them attractive for their usage in wound healing therapy. Alginate and chitosan have been used to develop novel wound healing and smart biomaterials due to various functionalities such as reducing swelling, non-toxic nature, biocompatibility, antimicrobial potential, and maintenance moist environment, ability to absorb wound fluid, and skin regeneration promotion. Functionalization of polysaccharides is one of the many approaches that have been used to modify and enhance the wound healing properties of these biomaterials. Many studies have been done to modify the polysaccharide hydrogels. Some of these are highlighted in this paper. The designing and development of smart hydrogels that react to their environment have recently sparked a significant scientific and pharmaceutical interest. Smart hydrogel development has been the primary focal area for developing highly advanced and sophisticated wound healing therapeutic technologies. This paper seeks to comprehensively shed light on the advancements of functionalized chitosan and alginate-based hydrogels and their applicability in wound healing therapeutics. In addition to this, thus identifying critical drawbacks faced in existing hydrogel systems and how prospective technologies enable digitally controlled bio-platforms coupled with biomaterials to improve wound care. This review hopes to stimulate and encourage researchers to identify future avenues worth investigation.